Pengaruh Gaya Belajar Terhadap Peningkatan Hasil Belajar Peserta Didik Materi Teks Biografi - Moh Hudhori (Journal of Classroom Action Research, 2023)
The background of this research is that the learning outcomes of students are not optimal, especially for materials that require narrative elaboration such as biographical text material. To overcome this through classroom action research, researchers utilize various learning styles in the hope of increasing student learning outcomes in biographical text material. This research is limited to biographical text material for Indonesian language lessons in Class X-9 at SMA Negeri 1 Menganti. This study used classroom action research methods with data collection techniques by observation, interviews and tests. The target for achieving an increase in learning outcomes is 75% classical completeness score with a minimum mastery of 65. The research implementation took place in 2 (two) cycles with varying changes in learning outcomes. In the first cycle of class X - 9 the learning outcomes achieved were 91.87% of the classical completeness score with an average achievement of 78.81, while in the second cycle the learning outcomes achieved in class X - 9 were 100% of the classical completeness score with an average achievement 86,17. From these results it can be concluded that the application of learning styles can affect the improvement of student learning outcomes in biographical text material. The percentage of positive responses of students carrying out learning by applying various learning styles was 92.96%, while the negative responses were 7.04%, so based on these results that the positive percentage was greater than negative, so students were interested in applying learning styles to improve student learning outcomes